RELIABILITY OF AIR SEPARATION MODULE COMPONENTS ON THE NITROGEN GENERATION SYSTEM OF BOEING AIRCRAFT - Kurniawan, Wahyu (Institut Teknologi Dirgantara Adisutjipto, 2021)
Aircraft is a type of transportation that can reach a certain area in a short time compared to other types of transportation. Every aircraft used will experience a decrease in performance along with the use of flight hours, to maintain and restore the aircraft condition to its original condition, maintenance effectiveness is needed. Aircraft maintenance carried out to keep the aircraft systems or components working properly, one of the components that need maintenance is the Air Separation Module. The purpose of this study to determine the reliability, failure rate, type of failure, and effectiveness of maintenance of the Air Separation Module.